Compartmentalization of acute phase reactants Interleukin-6, C-Reactive Protein and Procalcitonin as biomarkers of intra-amniotic infection and chorioamnionitis. Issue 2 (December 2015) - Dulay, Antonette T.; Buhimschi, Irina A.; Zhao, Guomao; Bahtiyar, Mert O.; Thung, Stephen F.; Cackovic, Michael; Buhimschi, Catalin S.
Graphical abstract: Highlights: Intra-amniotic infection is an underdiagnosed cause of preterm birth. Amniotic fluid infection most often progresses silently. Clinical chorioamnionitis does not reflect in elevated maternal cytokinemia. Maternal inflammatory markers have limited diagnostic value for chorioamnionitis. Decisions for expectant management or delivery require analysis of amniotic fluid. Abstract: Background: The arsenal of maternal and amniotic fluid (AF) immune response to local or systemic infection includes among others the acute-phase reactants IL-6, C-Reactive Protein (CRP) and Procalcitonin (PCT). If these molecules can be used as non-invasive biomarkers of intra-amniotic infection (IAI) in the subclinical phase of the disease remains incompletely known. Methods: We used time-matched maternal serum, urine and AF from 100 pregnant women who had an amniocentesis to rule out IAI in the setting of preterm labor, PPROM or systemic inflammatory response (SIR: pyelonephritis, appendicitis, pneumonia) to infection. Cord blood was analyzed in a subgroup of cases. We used sensitive immunoassays to quantify the levels of inflammatory markers in the maternal blood, urine and AF compartment. Microbiological testing and placental pathology was used to establish infection and histological chorioamnionitis. Results: PCT was not a useful biomarker of IAI in any of the studied compartments. Maternal blood IL-6 and CRP levels were elevated in women with subclinical IAI. Compared to clinically manifest chorioamnionitis group, women with SIR have higher maternal blood IL-6 levels rendering some marginal diagnostic benefit for this condition. Urine was not a useful biological sample for assessment of IAI using either of these three inflammatory biomarkers. Conclusions: In women with subclinical IAI, the large overlapping confidence intervals and different cut-offs for the maternal blood levels of IL-6, CRP and PCT likely make interpretation of their absolute values difficult for clinical decision-making.